Гендерный аспект невербальной коммуникации - Котелевец, К. А. (ХНУРЕ, 2020)
This work examines one of the most popular issues of modern psychology, understanding the object of non-verbal communication, manifestations in life, comparative features of gender.
Keywords: философия; гендерный аспект невербальной коммуникации